2021
DOI: 10.3389/fimmu.2021.685213
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Gene Expression Signature in Patients With Distinct Glioma Grades

Abstract: BackgroundGlioma is the most common type of primary brain tumor in adults. Patients with the most malignant form have an overall survival time of <16 months. Although considerable progress has been made in defining the adapted therapeutic strategies, measures to counteract tumor escape have not kept pace, due to the developed resistance of malignant glioma. In fact, identifying the nature and role of distinct tumor-infiltrating immune cells in glioma patients would decipher potential mechanisms behind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Notably, RORC expression had prognostic value in some cancers, especially KIRC, LGG, and MESO. Consistently, Ait Ssi et al ( Ait Ssi et al, 2021 ) found that RORC expression is upregulated in LGG patients with a poor prognosis. In conclusion, RORC expression can be an important regulator of cancers and RORC has prognostic value in some cancers.…”
Section: Discussionsupporting
confidence: 52%
“…Notably, RORC expression had prognostic value in some cancers, especially KIRC, LGG, and MESO. Consistently, Ait Ssi et al ( Ait Ssi et al, 2021 ) found that RORC expression is upregulated in LGG patients with a poor prognosis. In conclusion, RORC expression can be an important regulator of cancers and RORC has prognostic value in some cancers.…”
Section: Discussionsupporting
confidence: 52%
“…Chraa et al reviewed the tumor microenvironment and its infiltration by distinct T lymphocyte subpopulations 33 . This report explained the association of these different subtypes with cancer progression 33 , 34 . However, treatment with several cytokines, including IFN-γ, IL-2, IL-4, and IL-6, did not raise VISTA expression in tumor cells 35 .…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have advocated that pro-inflammatory M1 phenotype—associated with upregulation of CD115 and Siglec and consecutive production of IL-1β, IL-6, or IFN-γ—is critical for tumor eradication ( 39 ), especially since M1 phenotype has been reported to correlate with favorable survival outcomes in many human cancers ( 47 ). However, this trend appears inconsistent in glioma as inhibitory immune checkpoints such as PD-1, CTLA-4 and TIM-3 are consistently upregulated in M1/M2 GAMs which have been shown to significantly decrease patient prognosis ( 48 , 49 ). Mice study has revealed that disruption of GBM-derived IL-6, known to induce myeloid PD-L1, reduces local and systemic myeloid-driven immunosuppression ( 50 ).…”
Section: Glioma-associated Microglia/macrophages (Gams)mentioning
confidence: 99%